Studi Pola Lingkaran Pertumbuhan Otolith pada Ikan Katung (Pristolepis grooti) yang Ditangkap di Hilir Sungai Siak Provinsi Riau - Chahyadi, Ennie; Windarti, Windarti (Jurnal Perikanan dan Kelautan, 2016)
In the Siak River, Riau, the water quality in the downstream area is relatively bad due to pollutant originated from several sources such as industrial and domestic wastes. The low quality water may negatively affects the growth of fish and it is reflected in the growth pattern in the otolith of fish living in that river. To understand the growth pattern in the otolith of Pristolepis grooti (Anabantidae)living in that river, a study has been conducted. Totally 25 fishes were captured from the downstream of the Siak River. The otolith were then removed and processed following Windarti (2007) and investigated under a binocular microscope to study the growth ring pattern in the otolith. The number of dark growth ring was counted. Results shown that 2 to 5 dark growth rings, around 0.086 mm thick were present in the otolith of the fish. The presence of the dark growth rings in the otolith indicated that the growth of P. grooti in the downstream of the Siak River was hampered and this fact also suggested that the water quality in the downstream of the Siak River is not sufficient to support the life P. grooti in that area.